Pengaruh Gaya Hidup Terhadap Willingness To Subscribe Pada Applikasi Streaming Film Online Netflix di Kalangan Generasi Z Kota Surabaya - Hawari, Ahmad Nanang (Universitas Negeri Surabaya, 2023)
This research aims to analyze the influence of lifestyle on willingness to subscribe to the Netflix application among Generation Z, who are the most users of new media in the city of Surabaya. The number of respondents who became the sample in this research were 100 people. The method used in determining the sample is random purposive sampling, with a simple regression analysis method to process the data in this research. The results of the research indicate that the lifestyle variable has a significant influence on the variable of willingness to subscribe to the Netflix online movie streaming application. Based on the results of the t test, the results of the t count are 4,400 > t table of 0.197. Based on the results of the calculation of the Coefficient of Determination (R Square) of 0.165 or 16.5% which explains that the lifestyle variable (X) only has an influence of 16.5% on willingness to subscribe (Y) while the remaining 83.5% is influenced by the variable others that were not included in this research.